2020
DOI: 10.46244/geej.v7i2.1022
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Critical Thinking Ability in Listening Skill

Abstract: The present study analysed university students’ critical thinking ability on their listening skills. With this purpose in mind, 25 students taking listening subject participated in the study were chosen as the sample of this study. To gather the data, the essay test of critical thinking skill developed by Facione were administered to the participants after they had listened to related audio of conversation and/or monologue. The obtained data were then analysed using holistic critical thinking scoring rubric. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…They had a negative attitude toward GBA. This finding is also at odds with the conclusions of several previous studies, which concluded that the application of GBA was ineffective because fewer than fifty percent of students achieve passing grades in English classes, even though their teachers followed every stage of the genre-based approach (Nainggolan, 2018;Tachia & Loeneto, 2018). To further affirm the previous findings, Slamet (2015) stated the use of genre in teaching English has not been effective yet.…”
Section: Efl Teachers' Perception Of Gba Practicesmentioning
confidence: 64%
See 1 more Smart Citation
“…They had a negative attitude toward GBA. This finding is also at odds with the conclusions of several previous studies, which concluded that the application of GBA was ineffective because fewer than fifty percent of students achieve passing grades in English classes, even though their teachers followed every stage of the genre-based approach (Nainggolan, 2018;Tachia & Loeneto, 2018). To further affirm the previous findings, Slamet (2015) stated the use of genre in teaching English has not been effective yet.…”
Section: Efl Teachers' Perception Of Gba Practicesmentioning
confidence: 64%
“…Numerous investigations have been conducted within the scope of the GBA, starting from its implementation through genre-based teaching (GBT) to improve the four language skills in English as foreign language (EFL) classroom practice to other fields throughout the world (Kay & Dudley-Evans, 1998;Mohlabi-Tlaka et al, 2017;Mthembu-Funeka, 2009;Mumba & Mkandawire, 2019). Since its adaptation into the national English curriculum of Indonesian secondary schools Journal on English as a Foreign Language, 13(2), 475-498 p-ISSN 2088-1657e-ISSN 2502-6615 in 2004 and 2006, many Indonesian scholars have been interested in this approach and have done research related to this approach (Arimbawa, 2012;Mahfud, 2011;Nainggolan, 2018;Triastuti & Riazi, 2020;Triastuti et al, 2022).…”
Section: Genre-based Approach In Efl Classroommentioning
confidence: 99%